2009
DOI: 10.4049/jimmunol.0902033
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Bispecific Single-Chain Fragment Variable Specific for HLA Class II and FcαRI (CD89) Recruits Polymorphonuclear Neutrophils for Efficient Lysis of Malignant B Lymphoid Cells

Abstract: Bispecific Abs offer new perspectives for cancer immunotherapy. In this study, we describe a recombinant bispecific single-chain fragment variable (bsscFv) directed against FcαRI (CD89) on polymorphonuclear neutrophils (PMNs) or monocytes/macrophages and HLA class II on lymphoma target cells. FcαRI and HLA class II-directed single-chain fragment variable (scFv) fragments were isolated from phage display libraries, established from the hybridomas A77 and F3.3, respectively. The two scFv molecules were connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…GM-CSF enhanced the anti-tumor neutrophil-dependent ADCC through enhanced expression of CD11/CD18 molecules [336]. Neutrophils were also shown to contribute to the anti-tumor ADCC in Non-Hodgkin's Lymphoma using antibodies to CD20 (Rituximab) [341], in breast cancer using a Tn antigen-specific chimeric mAb [342], and in B-cell lymphoma using a bispecific singlechain fragment variable-specific for HLA class II and FcαRI (CD89) [343]. The bispecific antibody against the myeloid receptor for IgA (FcαR1; CD89) and the B-cell surface marker CD20 induced neutrophil-dependent ADCC toward broad range of B cell lines [344].…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
“…GM-CSF enhanced the anti-tumor neutrophil-dependent ADCC through enhanced expression of CD11/CD18 molecules [336]. Neutrophils were also shown to contribute to the anti-tumor ADCC in Non-Hodgkin's Lymphoma using antibodies to CD20 (Rituximab) [341], in breast cancer using a Tn antigen-specific chimeric mAb [342], and in B-cell lymphoma using a bispecific singlechain fragment variable-specific for HLA class II and FcαRI (CD89) [343]. The bispecific antibody against the myeloid receptor for IgA (FcαR1; CD89) and the B-cell surface marker CD20 induced neutrophil-dependent ADCC toward broad range of B cell lines [344].…”
Section: Antibody-dependent Cell-mediated Cytotoxicity (Adcc)mentioning
confidence: 99%
“…The first are F(ab') 2 conjugates targeting the tumor antigens HER2/neu or CD30, respectively. The second is a bispecific ab targeting the EGFR, and the third a tandem bispecific single chain Fv (bsscFv) targeting HLA class II [39,[45][46][47]. All of these agents mediated ADCC in vitro by recruiting CD89-positive effector cells, i.e., mainly neutrophilic granulocytes and monocytes.…”
Section: Examples Of Ab-derived Agents Recruiting Effector Cells Othementioning
confidence: 99%
“…Moreover, it has now been demonstrated that FcαRI is the most potent neutrophil Fc receptor compared to Fcγ receptors for the induction of antibody-dependent killing of tumor cells (Deo et al, 1998;Huls et al, 1999aHuls et al, , 1999bvan Egmond et al, 1999a;Keler et al, 2000;Stockmeyer et al, 2000;Dechant and Valerius, 2001;Stockmeyer et al, 2001;Dechant et al, 2002;Stadick et al, 2002;Stockmeyer et al, 2003;Dechant et al, 2007;Zhao et al, 2008;Guettinger et al, 2010;Lohse et al, 2010). Furthermore, cross-linking of neutrophil FcαRI by (dimeric) IgA leads to the release of LTB4 and neutrophil recruitment, resulting in amplification of neutrophil migration (van der Steen et al, 2009).…”
Section: Fcαri Signaling and Functionsmentioning
confidence: 97%